Iodinated Metallacrowns: Toward Combined Bimodal Near‐Infrared and X‐Ray Contrast Imaging Agents. Issue 6 (21st January 2020) - Lutter, Jacob C.; Eliseeva, Svetlana V.; Collet, Guillaume; Martinić, Ivana; Kampf, Jeff W.; Schneider, Bernadette L.; Carichner, Aidan; Sobilo, Julien; Lerondel, Stéphanie; Petoud, Stéphane; Pecoraro, Vincent L.
Abstract: Multimodal probes capable of combining imaging modalities within a single molecule are in high demand today as they can provide information at both molecular and anatomical levels. Herein, a study was conducted on a series of gallium(III)/lanthanide(III) bis(12‐MC‐4) metallacrowns (MCs) with the general composition Ln[12‐MCGa III N(shi) ‐4]2 (iph)4 (Ln‐I x, x= 0, 4, 8, 12), where shi and iph are salicylhydroximate and isophthalate ligands, respectively, or their iodinated derivatives. For Yb‐I x, the attenuation in X‐ray computed tomography (XCT) imaging and near‐infrared (NIR) luminescence properties can be finely tuned by controlled structural modifications based on iodo groups. Solutions of Yb‐I x appear to be 22–40 times more efficient as XCT agents in comparison to the commercially available iobitridol, while providing an intense emission signal in the NIR range with total quantum yields up to 8.6 %, which are among the highest values reported so far. Therefore, these molecules are promising potential bimodal agents for combined NIR luminescence and XCT imaging. Abstract : A new family of iodinated ytterbium(III)‐gallium(III) metallacrowns with tunable X‐Ray attenuation and near‐infrared luminescence has been created.